Литература и сетература в Рулинете(Literature and «the network literature» in the Russian literary Internet) - Zubchenko, Irina (Poljarnyj vestnik, 2007)
From the beginning the Russian Internet has received its peculiar literary character due to a large number of sites with open publication access. This paper offers a brief history of the Russian literary Internet and provides an analysis of different aspects of the term «network literature» (called «seteratura» in Russian). Comparing electronic and paper versions of the same texts, the author argues that the term «seteratura» is appropriate only for specific types of network literature.